(untitled) (Neo Science Peer Reviewed Journal, 2023)
This is due to the fact that the wear and tear of industrial equipment in thermal power plants is on average 91.73 percent. In 2015, "Uzbek¬energo" condensing thermal power plants had an efficiency of 28.4-42%, and the average was 33.5%. This is 1.5 times less than the indicators of modern thermal power plants of this type used in the European Union, Southeast Asia. Naturally, 1 kW. more heat and energy resources are used to produce electricity per hour compared to foreign electricity producers. For example, in 2015, 1 kW in modern thermal power plants of European Union countries. 269 grams of conventional fuel are used to generate electricity per hour, while this indicator reaches almost 374.9 grams in thermal power plants of "Uzbekenergo" JSC.